2019
DOI: 10.1007/s00213-019-05378-x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired empathy and increased anger following social exclusion in non-intoxicated opioid users

Abstract: Rationale Social functioning is modulated by the endogenous opioid system. In opioid use disorder, social functioning appears disrupted, but little research has delineated the nature of these deficits and their relationship to acute opioid use. Objectives The current study aimed to assess both emotional and cognitive empathy, along with subjective and physiological responses to social exclusion in opioid users who were either acutely intoxicated or non-intoxicated from using opioids. Methods Individuals on an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…For the first path of this indirect effect, the results of this study were consistent with the prior studies. Some scholars have indicated that social exclusion is not only a direct predictor of self-control ( Crescioni and Baumeister, 2009 ; Burson et al, 2012 ; Xiaojun et al, 2017 ), but can also contribute to negative affects and experiences such as loneliness, depression, and anger ( Fung et al, 2016 ; Feng et al, 2019 ; Carlyle et al, 2020 ; Arslan, 2021 ), which will indirectly decrease self-control ( Chester et al, 2016 ). This might be because social exclusion threatens individuals’ basic psychological requirements ( Williams, 2009 ; Baumeister, 2011 ), which will motivate people to do something actively to compensate for their psychological distress or find some substitutes to console themselves.…”
Section: Discussionmentioning
confidence: 99%
“…For the first path of this indirect effect, the results of this study were consistent with the prior studies. Some scholars have indicated that social exclusion is not only a direct predictor of self-control ( Crescioni and Baumeister, 2009 ; Burson et al, 2012 ; Xiaojun et al, 2017 ), but can also contribute to negative affects and experiences such as loneliness, depression, and anger ( Fung et al, 2016 ; Feng et al, 2019 ; Carlyle et al, 2020 ; Arslan, 2021 ), which will indirectly decrease self-control ( Chester et al, 2016 ). This might be because social exclusion threatens individuals’ basic psychological requirements ( Williams, 2009 ; Baumeister, 2011 ), which will motivate people to do something actively to compensate for their psychological distress or find some substitutes to console themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our NMPOU sample was less affected by confounding factors, which are commonly accompanied by individuals with current or former heroin use (e.g., pre‐existing brain injuries due to hypoxia following overdose‐induced coma, or viral infections such as hepatitis C [HCV] and human immune‐deficiency virus [HIV] caused by intravenous injection; Byrd et al., 2013; Darke, 2011; Mintzer & Johnson, 2007; Yarlott et al., 2017). This might further explain the different empathy results of the MET between our NMPOU group and a recent study reporting impaired affective empathy in nonintoxicated opioid substituted patients with former heroin use (Carlyle et al., 2020). Fifth, we controlled for trait empathy by using the IRI showing no group differences and no correlation with empathy for pain.…”
Section: Discussionmentioning
confidence: 52%
“…Similarly, a review from Iran found a high prevalence of domestic violence in those with drug use disorders [28]. The association of opioid use with violence appears to be complicated, involving biological as well as social and characterological factors [29, 30].…”
Section: Discussionmentioning
confidence: 99%